The Effect using Rhizoctonia Mycorrhizaee on Dendrobium nandia anindhita Seedling - R Soelistijono; K Aprilliyan; Daryanti Daryanti (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2021)
Dendrobium nandia anindhita orchid is a favored hybrid of orchid because it flowers easyly and has high variety of flower colors. The aim of this study was to determine the effect of the application of Rhizoctonia mycorrhizaee on seedling Dendrobium hybrid orchids. It is expected that the seedling will have the characteristics of the Dendrobium orchid species. The research was carried out in a green house and laboratory of the Faculty of Agriculture, Tunas Pembangunan University. The design used was a completely randomized design with one variable and 25 seedling samples each. The results showed: (1) Microscopically, Rhizoctonia mycorrhizaee had the following characteristics: Fungal hyphae growing on PDA media were white, branches of Rhizoctonia mycorrhizaee hyphae formed elbows and had septa; (2) The application treatment of Rhizoctonia mycorrhizaee (M) had a significant effect on the parameters of plant height, number of leaves, number of roots, root length and plant fresh weight, treatment (M) had no significant effect on parameters of leaf length; (3) Morphological observations showed that the orchid plants that were applied to Rhizcotonia mycorrhizae had greener leaf colors, more leaves, and longer roots than those without Rhizcotonia mycorrhizae.